Unsur Mistis Dalam Novel-Novel Karya Neno Cristiandi Nelis dan Implikasinya pada Pembelajaran di SMA (Tinjauan Antropologi Sastra) - Santiani Santiani; Petrus Poerwadi; Misnawati Misnawati; Siti Supriyati; Sri Maya (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
Mystical is a spiritual effort in realizing the social relations that prevail in society. Mystical as an understanding that gives teachings that are secret or all-secret, hidden, dark, and veiled in darkness, so that they are only known, known, or understood by certain people,especially their adherents. This study aims to describe the mystical forms and beliefs of the Ma'anyan Dayak people towards mystical matters including: (1)Mystical forms in the novels Minyak Bintang, Dalung, and Kariau (2) Public beliefs in mystical elements contained in the novels Minyak Bintang, Dalung, and Kariau (3) implications for literature learning in high school class XII. This research approach uses a qualitative research approach using descriptive methods. The data sources used in this study are Novels, Wawaacara, and field notes. The data in this study are Neno Cristiandi Neno's novel Minyak Bintang, Dalung, and Kariau and interviews with speakers conducted in Jaweten Village and Garinsing Village, East Barito Regency. Data analysis of this study was analyzed by reducing data, presenting data, and drawing conclusions. The results of research on mystical forms and people's belief in mystical things and implications for literature learning in high school show (1) How mystical forms in the novels Minyak Bintang, Dalung, and Kariau. (2) there are five mystical forms(3) there are three public beliefs in mystical things. The results of this study can be used in novel learning in high school class XII, especially in competency 3.8. interpreting the author's view of life in the novel being read.